Magnetically‐Assisted 3D Bioprinting of Anisotropic Tissue‐Mimetic Constructs. (17th October 2022) - Pardo, Alberto; Bakht, Syeda Mahwish; Gomez‐Florit, Manuel; Rial, Ramón; Monteiro, Rosa F.; Teixeira, Simão P. B.; Taboada, Pablo; Reis, Rui L.; Domingues, Rui M. A.; Gomes, Manuela E.
Abstract: Recreating the extracellular matrix organization and cellular patterns of anisotropic tissues in bioengineered constructs remains a significant biofabrication challenge. Magnetically‐assisted 3D bioprinting strategies can be exploited to fabricate biomimetic scaffolding systems, but they fail to provide control over the distribution of magnetic materials incorporated in the bioinks while preserving the fidelity of the designed composites. To overcome this dichotomy, the concepts of magnetically‐ and matrix‐assisted 3D bioprinting are combined here. By allowing low viscosity bioinks to remain uncrosslinked after printing, this approach enables the arrangement of incorporated magnetically‐responsive microfibers without compromising the resolution of printed structures before inducing their solidification. Moreover, the fine design of these magnetic microfillers allows the use of low inorganic contents and weak magnetic field strengths, minimizing the potentially associated risks. This strategy is evaluated for tendon tissue engineering purposes, demonstrating that the synergy between the biochemical and biophysical cues stemming from a tendon‐like anisotropic fibrous microstructure, combined with remote magneto‐mechanical stimulation during in vitro maturation, is effective on directing the fate of the encapsulated human adipose‐derived stem cells toward tenogenic phenotype. In summary, the developed strategy allows the fabrication of anisotropic high‐resolution magnetic composites with remote stimulation functionalities, opening new horizons for tissue engineering applications. Abstract : The concepts of magnetically‐ and matrix‐assisted 3D bioprinting are combined for the fabrication of high‐resolution biomimetic constructs with anisotropic microstructure. The designed magnetic composites resemble the 3D fibrillar structure of tendon tissues, also allowing their magneto‐mechanical stimulation during maturation process, thus providing the encapsulated cells with the adequate biophysical and biochemical cues to induce their elongated growth and tenogenic commitment.